Junie B. Jones and some sneaky peeky spying - Park, Barbara; Brunkus, Denise (New York : Random House, 1994)
Six-year-old Junie B.'s penchant for spying on people and her curiosity about the private life of her teacher get her in trouble at kindergarten.
Series title and number from v. 5.
"A First stepping stone book."
Keywords: Kindergarten -- Fiction; Schools -- Fiction; Teachers -- Fiction; Humorous stories